RF Cyber Range: Building Communication Scenarios Using Software-Defined Radio for Radio Frequency Vulnerability Analysis - Araújo, Patrícia R.; Bortoloto, Raul G. O.; Faria, Décio R. M.; Gomes, Otávio S. M. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
The 433 MHz frequency band is widely used by low-cost wireless devices such as sensors and alarm systems, but it often lacks robust security mechanisms. This work proposes the construction of communication scenarios for vulnerability analysis in RF devices using software-defined radios (SDR). The methodology combines scientometric analysis, a survey of vulnerabilities from CVE databases, and both simulated and practical experiments using GNU Radio and RTL-SDR. The results demonstrate the feasibility of attacks such as jamming and replay, highlighting the risks associated with the absence of authentication and encryption in these devices. Results highlight the need for RF security and validate SDR for vulnerability testing.